Mineral N dynamics in bare and cropped Leucaena leucocephala and Dactyladenia barteri alley cropping systems after the addition of 15Nlabelled leaf residues - Vanlauwe, Bernard; Diels, J.; Duchateau, L.; Sanginga, N.; Merckx, Roel (1998)
In tropical cropping systems with few external imputs, efficient management of mineral N derived from added organic residues is essential for the proper functioning of the system. We studied the dynamics of mineral Nitroden (N) in the top 100 cm of soil with a system tensiometers and suction cups after applying 15N-labelled Leucaena Leucocephala and Dactyladenia bacteria residues to bare and cropped microplots installed in the respective alley cropping systems, and folloed the fate of the N for two maize-cowpea rotations (1992 and 1993). Fifty days after applying the residues (DAA), 20% of the added residue N was found in the soil profile of the bare Leucaena treatment and 5% under Dactyladenia, compared with 5% and 1%, respectively, where cropped. All values decreased to about 1% after 505 days. In the cropped soil, no mineral N derived from the residues was lost by leaching during the first 6 weeks. As the maize grew, the soil profile was gradually depleted of nitrate to near zero in the Dactyladenia treatment, whereas during the cowpea season the amount of nitrate N increased to 36 kg N ha-1 for the Leucaena treatment, and 26 kg N ha-1 for the Dactyladenia treatment. The soil of the bare microplots contained substantially more nitrate N (98 and 47 kg N ha-1 during the first year on average, under Luecaena and Dactyladenia, respectively) than that of the cropped microplots, except during 1993 cowpea season. Nitrate residing in the subsoil (80-100 cm) in the bare treatmentwas not readily leached to deeper soil. The risk of losses of native mineral N was greater during the first 50 DAA and to a lesser extent during the cowpea seasons. Improved management of the hedgerows could increase the potential of the hedgerow trees to recycle mineral N.